TRADE, ECONOMIC, AND INVESTMENT COOPERATION BETWEEN KAZAKHSTAN AND ARMENIA: STATUS AND PROSPECTS - ADILBAYEV, Zhalgas; KOZHIROVA, Svetlana (CENTRAL ASIA AND THE CAUCASUS, 2018)
This article presents a brief overview of the current status of trade, economic, and investment cooperation between Kazakhstan and Armenia, integration processes between the two countries in the Eurasian space, priority areas of their foreign economic policy, and cooperation prospects. Since the early 1990s, the Republic of Kazakhstan and the Republic of Armenia have worked to build bilateral relations by establishing clear political and economic priorities and setting strategic goals in order to promote Kazakhstan’s national interests in the South Caucasian region and Armenia’s national interests in Central Asia. This in turn has made it possible to fill the agenda of relations between the two countries with concrete practical content. After gaining independence, the former Soviet republics were faced with a number of difficult foreign policy problems, including that of developing trade, economic, and investment cooperation on a new basis. The need to look for ways to develop further cooperation was dictated by the existence of common problems. For Armenia, the countries of Central Asia are of particular importance in this respect, and Kazakhstan has a major role to play here as a long-term trade and economic partner, a country with economic potential, rich natural resources, and a promising market. Considering the situation in these two countries, one can say that there are prospects for the development not only of political, but also of trade, economic, and investment cooperation. The first thing to note is that political cooperation between the two countries provides a good legal basis for expanding cooperation and tapping its full potential in every area, including the trade and economic sphere. At present, trade and economic relations between Kazakhstan and Armenia are not yet fully developed for a number of geopolitical reasons. On the one hand, virtually all transport and logistics routes in the South Caucasian region are blocked by Turkey, Azerbaijan, and partly by Georgia in view of strained relations with Russia. The lifting of international sanctions against Iran points to the possibility of new transport corridors of paramount importance to Armenia being initiated in the region. In this context, Armenia will continue its close cooperation with Iran in the medium term to create the necessary prerequisites for gaining access to the markets of the Middle East and Persian Gulf countries. Kazakhstan, for its part, is also taking steps to enter the Iranian market, including through the Caspian Sea. In 2017, it announced the construction of a transport hub port in Western Iran. In addition, freight trains are now running from Kazakhstan through Turkmenistan to the Iranian city of Gorgan. Kazakhstan and Armenia could focus their efforts on combining mutually beneficial economic projects using Tehran’s entire potential. One of the most attractive transport and logistics projects is the Silk Road, which is being actively implemented by the Beijing authorities. For example, Kazakhstan has already launched a number of government programs somehow connected with the implementation of the Chinese Silk Road initiative. Armenia is also negotiating with the Chinese on its possible participation in this project, which can solve many transportation problems that currently exist in the South Caucasian region.